1998
DOI: 10.1103/physrevb.57.r12701
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of the Si(001)c(4×4)-Sb surface

Abstract: Results of low-energy electron diffraction, Auger electron diffraction, low-energy ion scattering, and ab initio pseudopotential studies of submonolayer coverages of Sb on the Si͑001͒ surface indicate the existence of an ordered c(4ϫ4)-Sb reconstruction between 0.2 and 0.3 ML. Analysis of the ion-scattering data from this surface suggests an overlaid above-row structure in which Sb dimers are situated directly above Si dimer rows. Ab initio pseudopotential calculations support this conclusion and confirm that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…CAICISS has proven to be useful in exploring surfaces and subsurface structures [14][15][16][17][18][19][20][21]. It has been revealed that Fe(1 1 1) thin films with a bcc-type structure can be epitaxially grown on a Si(1 1 1) crystal even at room temperature (RT) and form a single-domain structure.…”
Section: Introductionmentioning
confidence: 99%
“…CAICISS has proven to be useful in exploring surfaces and subsurface structures [14][15][16][17][18][19][20][21]. It has been revealed that Fe(1 1 1) thin films with a bcc-type structure can be epitaxially grown on a Si(1 1 1) crystal even at room temperature (RT) and form a single-domain structure.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study considered three plausible geometries for the Sb dimers for the 1/4 ML covered Sb/Si(0 0 1) system within an ordered c(4 · 4) reconstruction [17]. Within this surface reconstruction, three plausible overlayer dimer geometries were considered, and it was concluded that the minimum energy configuration corresponds to an overlaid above-row structure.…”
Section: /4 ML Coveragementioning
confidence: 99%
“…However, in an earlier scanning tunneling microscopy and surface extended X-ray absorption fine structure study [6] it is shown that Sb dimers occupy modified bridge sites on the Si(0 0 1) surface perpendicular to the clean Si dimers for an Sb coverage of 1.0 ML. A 0.25 ML c(4 · 4) surface phase, in an 'overlaid above-row structure' formed by Sb dimers adsorbed directly above the underlying Si dimer rows, has also been recently observed [7][8][9][10] for this Sb/Si(0 0 1)-(2 · 1) system.…”
mentioning
confidence: 95%
“…1d. Recent ab initio pseudopotential density functional calculations [8,9] for this c(4 · 4) phase have inferred an overlaid above row structure as the energetically most favorable configuration. In this arrangement three out of every four dimers in the 1.0 ML covered Sb adlayer are removed, leaving an array of Sb dimers bonded above the partially reformed Si dimer rows in a c(4 · 4) structure [8,18] in the 0.2-0.3 ML Sb coverage range.…”
mentioning
confidence: 99%
See 1 more Smart Citation